Judicial delimitation of immunity from jurisdiction in social jurisdiction - Juárez Pérez, Pilar (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
With a deep-rooted tradition and extensive legal history, the figure of immunity from jurisdiction has been the subject of a notable legislative and jurisprudential evolution, which has attempted to adapt this institution to changes in the conception of state sovereignty and legal-private relations experienced by States over the years. This evolution is reflected with special clarity in the field of relationships derived from the international employment contract, where States have often interpreted immunity with reprehensible breadth, as a shielding tactic against the demands of their workers. In this scenario, Spanish jurisprudence has developed a task that is a complex as it is necessary, which has a double purpose: combating this abusive practice and clarifying the Spanish regulation that could be improved on immunity from jurisdiction and individual employment contracts.